Traditions of the Tuvan artisan Saayalar kinship group - Oorzhak , Valeriy O. (The New Research of Tuva, 2022)
This article is a study of a composition of a separate kinship group of Tuvans following traditional pursuits and skills — shever Saayalar aal-aimaa (the family of the skilful (artisans) Saaya). The author belongs to the group as well. For our sources, we have used personal observations, field materials, memories and talks of the older generation. The Shever Saayalar stand closer to the Aksy-Barlyk Saayalar of the Barun-Khemchig rayon. Besides Aksy-Barlyk, they have lived in such settlements as Azhyg-Kara-Sug, Chaylag-Oyum, Ak-Sug, Kyshtag-Oyum, Kөzheelig, and Kөөp-Sөөk of the Bay-Taygin rayon. Recently, some of the families moved to Kyzyl-Mazhalyk (Barun-Khemchig rayon), or to such towns and cities as Ak-Dovurak and Kyzyl, and to other rayons of the republic. Some members of the aimag live in other regions of Russia. The oldest and most widely known representative of the Shever Saayalar was Kogel Mizhiteyevich Saaya (1931–2021), member of the Union of Artists of the USSR. We provide information on the kinship group up to the seventh-generation ancestor Saaya Kara-Dargan (c. 1805–1855), as well as explain why the group is called Shever. Of special interest for us is the life of Dargan-Khelin (c. 1830–1905), a skilled blacksmith (dargan), who was a student in Tibet for many years and was awarded the Buddist degree of kheliң. Upon returning to his homeland, Dargan-Khelin made religious figurines, decoration for Buddhist temples, and jewellery, in addition to holding divine services. He passed on his skills to his children and grandchildren. Artisanship and common pursuits in life linked generations together, made kinfolk feel close to each other and stimulated them to strive for new forms of knowledge. The backbone of the group was preserved, and its members are taking on the artisanship and art they inherited from their ancestors to a new level.